Concept of Agrotourism in the Food Estate Project in Ria-Ria Village, Humbang Hasundutan Regency - Siagian, Morida; Sitorus, Rudolf; Talarosha, Basaria (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Utilization of agricultural potential as a tourist attraction becomes an added value in agricultural businesses today. Agrotourism becomes an alternative for tourists to get recreational experience, knowledge and business relationships in agriculture. For the community this activity can highlight and promote local culture, increase farmers' incomes and preserve natural resources. Ria-Ria village is one of the areas in Humbang Hasundutan Regency chosen by the Government as a food estate area. The area consists of 1000 hectares of land, 215 hectares of which have been planted with 3 types of horticultural plants, namely garlic, onions, and potatoes. But the design of food estate land is still focused on the development of agricultural activities, making the area not ready as an agricultural tourist destination. By socializing to the Ria-Ria Village farming group about the concept of agrotourism by displaying agrotourism references found in several regions, the community has the understanding, awareness and motivation to plan and work on agricultural tourism activities with local potential they have in the food estate area.